2023
DOI: 10.3390/nu15071740
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Intake and Risk of Cardiovascular Disease: A Systematic Review and Meta-Analysis of Prospective Studies

Abstract: The purpose of this study is to understand the conflicting results from previous studies on the association between carbohydrate intake and cardiovascular disease (CVD) by conducting a systematic review and meta-analysis to summarize the most recent scientific evidence. A systematic review used three electronic databases to gather literature on the association between carbohydrate intake and CVD. Considering the discrepancies, either fixed or random effect models were chosen to determine the effect size, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Sweetened beverages and refined carbohydrates are among the food categories with high pro-inflammatory potential, which may partly account for their harmful effects on cardiovascular health [19]. Furthermore, the dose-response relationship of carbohydrate intake and CV risk has been elucidated by a recent meta-analysis, which showed that the increased CV risk associated with carbohydrate intake was exacerbated when more than 60% of total energy was derived from carbohydrates, especially in Asian populations [20]. Current ESC guidelines for primary prevention recommend the restriction of free sugar consumption, particularly sugar-sweetened beverages, to a maximum of 10% of daily energy intake [14].…”
Section: Dietary Models and Cardiovascular Healthmentioning
confidence: 99%
“…Sweetened beverages and refined carbohydrates are among the food categories with high pro-inflammatory potential, which may partly account for their harmful effects on cardiovascular health [19]. Furthermore, the dose-response relationship of carbohydrate intake and CV risk has been elucidated by a recent meta-analysis, which showed that the increased CV risk associated with carbohydrate intake was exacerbated when more than 60% of total energy was derived from carbohydrates, especially in Asian populations [20]. Current ESC guidelines for primary prevention recommend the restriction of free sugar consumption, particularly sugar-sweetened beverages, to a maximum of 10% of daily energy intake [14].…”
Section: Dietary Models and Cardiovascular Healthmentioning
confidence: 99%
“…Fetal growth restriction also alters the response to sweet taste at birth (Ayres et al., 2012) and increases the preference for foods that are rich in sugars and fats starting in early life (Silveira et al., 2012) and continuing into adulthood (Barbieri et al., 2009; Kaseva et al., 2013; Lussana et al., 2008; Perala et al., 2012; Stein et al., 2009) in humans. Since alterations in eating habits may be associated with the development of metabolic disorders (Jo & Park, 2023; Layman et al., 2003; Li et al., 2023; Oh et al., 2005), continuous feeding unbalance over the life course of individuals exposed to in utero growth restriction might be a reason for the increased risk of developing these conditions (Portella & Silveira, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since alterations in eating habits may be associated with the development of metabolic disorders (Jo & Park, 2023;Layman et al, 2003;Li et al, 2023;Oh et al, 2005), continuous feeding unbalance over the life course of individuals exposed to in utero growth restriction might be a reason for the increased risk of developing these conditions (Portella & Silveira, 2014).…”
Section: Introductionmentioning
confidence: 99%